Steam Reforming of High-Concentration Toluene as a Model Biomass Tar Using a Nickel Catalyst Supported on Carbon Black - Soohyun Kim; Sangjun Yoon; Zulqarnain; Jiho Yoo; Hyuk Im; Sangdo Kim; Donghyuk Chun; Hokyung Choi; Jeonghwan Lim (Energies)
Biomass tar, an inevitable byproduct of biomass pyrolysis and gasification, poses a significant challenge due to its tendency to condense in pipelines, causing clogging and operational issues. Catalytic steam reforming can convert tar into syngas, addressing the tar issue while simultaneously producing hydrogen. However, the reforming catalyst is highly susceptible to deactivation by coking, especially when dealing with highly concentrated polymeric hydrocarbons such as tar. This study focused on enhancing the durability of tar-reforming catalysts. Nickel-based catalysts were prepared using carbon supports known for their high coking resistance, such as carbon black (CB), activated carbon (AC), and low-rank coal (LRC). Their performance was then tested for the steam reforming of high-concentration toluene, a representative tar. All three carbon supports (CB, AC, LRC) showed high catalytic performance with NiMg catalysts at 500 °C. Among them, the mesoporous CB support exhibited the highest stability when exposed to steam, with NiMg on CB (NiMg/CB) remaining stable for long-term continuous operation without any deactivation due to coking or thermal degradation.